Les dents moustériennes de la grotte Boccard, lieu-dit Bas-de-Morant (commune de Créancey, Côte-d'Or, Bourgogne) - Bruno Maureille; François Djindjian; Maria Dolorès Garralda; Alan E. Mann; Bernard Vandermeersch (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The Boccard cave is located in the Créancey municipality of the Côte-d’Or. A clear stratigraphy has been defined with a Mousterian layer in which three human permanent teeth were discovered: a lateral upper left incisor, an upper second right premolar and a lower second right molar. The metrical and morphological, descriptive and comparative studies of these remains enable us to integrate them within the variability of Neanderthal teeth and to exclude them from the variability of recent Homo sapiens sapiens. The Boccard cave teeth have no evidence of pathology, their dimensions are average and they present no special characteristics, except perhaps the lower molar, which may present a voluminous calciﬁcation of its pulp.